Adherence to treatment in older adults with Diabetes Mellitus. Medical Office 124 - González Baños, Yanara; Terrado Almarales, Osiris Oscar; Salgado Izquierdo, Maikel Santiago; Echevarria Cabrera, Eunice; Morejón Rosales, Yuday; Curbelo Fajardo, Juan Carlos (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: low adherence to treatment is a problem for the control of diabetes mellitus. It is a disease present due to its impact on morbidity and mortality in the country.Objective: to characterize adherence to treatment in older adults with diabetes mellitus at the 124th medical office of the Hermanos Cruz polyclinic in the municipality of Pinar del Río during the period from January 2021 to June 2023.Methods: an observational, descriptive, cross-sectional study was carried out; the universe was constituted by 138 older adults, a sample was selected by non-probabilistic sampling of 124 patients, theoretical and empirical methods were used, applying the questionnaire for the evaluation of therapeutic adherence and influential factors and descriptive statistics, using absolute and relative frequencies.Results: There was a predominance of older diabetic adults aged 70 years and over (62,1 %); 59,6 % were female, with a pre-university school level (54 %); with 48,4 % partial adherence to treatment, arterial hypertension as an associated chronic disease in 61,3 %, 29,8 % comply with the indicated diet, 31,4 % take the medication on the established schedule, the influential factor in non-compliance with treatment was forgetfulness in 71 %.Conclusions: older adults with diabetes mellitus had a predominance of partial adherence to treatment.